2019
DOI: 10.1073/pnas.1902704116
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical connectivity correlates selectively with attention’s effects on spatial choice bias

Abstract: Neural mechanisms of attention are extensively studied in the neocortex; comparatively little is known about how subcortical regions contribute to attention. The superior colliculus (SC) is an evolutionarily conserved, subcortical (midbrain) structure that has been implicated in controlling visuospatial attention. Yet how the SC contributes mechanistically to attention remains unknown. We investigated the role of the SC in attention, combining model-based psychophysics, diffusion imaging, and tractography in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 45 publications
1
18
2
Order By: Relevance
“…One possibility is that SC activity biases response choice without impacting sensory processing, as can be said of the effect of cueing on behavioral responses (6). A reanalysis of prior microstimulation studies within a signal detection framework ( 122), an analysis of interindividual differences in functional connectivity (fMRI) in the human (154), and correlations between SC activity and shifts in response criteria (20), suggest that the SC activity may impact target choice by shifting response criteria in favor of precued target locations, without generating a spatial bias in the global competition for sensory representation as suggested above (e.g., 116).…”
Section: The Superior Colliculusmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that SC activity biases response choice without impacting sensory processing, as can be said of the effect of cueing on behavioral responses (6). A reanalysis of prior microstimulation studies within a signal detection framework ( 122), an analysis of interindividual differences in functional connectivity (fMRI) in the human (154), and correlations between SC activity and shifts in response criteria (20), suggest that the SC activity may impact target choice by shifting response criteria in favor of precued target locations, without generating a spatial bias in the global competition for sensory representation as suggested above (e.g., 116).…”
Section: The Superior Colliculusmentioning
confidence: 99%
“…However, SC inactivation had no measurable effect on the cue-related attentional modulation observed in MST and MT, meaning that visual information must have been prioritized via alternative pathways, which do not involve the amplification of firing rates (115). Sreenivasan and Sridharan (154) suggested that in the human brain, there is no need to find such alternative pathways because the SC only affects target choice. In the monkey brain, however, recent inactivation studies using a paradigm to separate shifts in criterion from shifts in sensitivity (122,156) indicate the SC does enhance sensitivity in the task.…”
Section: The Superior Colliculusmentioning
confidence: 99%
“…Finally, some forms of attention appear to act in multiple ways on the same system. For example, visual attention is believed to both: (1) enhance the sensitivity of visual neurons in the cortex by modulating their activity and (2) change subcortical activity such that sensory information is readout differently (Birman and Gardner, 2019;Sreenivasan and Sridharan, 2019). In this way, attention uses two different mechanisms, in different parts of the brain, to create its effect.…”
Section: How To Enhance Performancementioning
confidence: 99%
“…Studies performed in non-human primates have also shown that the pulvinar (in the posterior thalamus and strongly connected with visual occipital regions), is involved in coordinating functional interactions across cortical areas for visual attention (Saalmann et al, 2012;Zhou et al, 2016). This region is also connected with the superior colliculus, a midbrain structure that enables both stimulus-driven and goal-driven attention across species (Friedrich et al, 2020;V. Sreenivasan & Sridharan, 2019).…”
Section: Table 1 White Matter Tracts Associated With Attention Workmentioning
confidence: 99%